Sacrificial carbon nitride-templated hollow FeCo-NC material for highly efficient oxygen reduction reaction and Al-air battery. (1st May 2020) - Wang, Yu; Zhang, Guoxin; Ma, Mang; Wang, Yiyan; Zhang, Ying; Sun, Xiaoming; Yan, Zifeng
Abstract: Solid-phase templates are commonly used for building hollow-structured carbon materials (CMs) but often demand post treatments to remove templates. Herein, we develop an efficient and general method to construct hollow carbonaceous structure via the templating of sacrificial carbon nitride (termed as f-NC) without post treatment. The f-NC template can be decomposed under high-temperature annealing, additionally, it can serve as N source to enrich the N content. Applying f-NC template, we manage the synthesis of hollow-structured highly dispersed binary FeCo-nitrogen-carbon material (termed as f-NC@FeCo-NC). Its hollow feature is confirmed by direct observation using HRTEM. Meanwhile, Fe/Co in oxidation states have been verified uniformly distributing in heavily N-doped CMs (N content ∼ 13.2 at.%). The resulted f-NC@FeCo-NC, as examined by electrochemical measurements, exhibits highly efficient performance toward oxygen reduction reaction (ORR) in alkaline medium. It respectively shows much enhanced onset and half-wave potentials of 1.01 and 0.89 V relative to the FeCo-NC that is obtained without f-NC, in contrast, 20 wt% Pt/C shows 0.95 V onset potential and 0.83 V half-wave potential. The f-NC@FeCo-NC catalyst also shows excellent Al-air battery performance when applied as cathode, which possesses a high open circuit voltage of 1.91 V and a high peak power density of 241 mW cm −2 . We believe this sacrificial f-NC can be applied as general template for the fabrication of other hollow-structured carbon-based materials for broad electrochemical applications.